2012
DOI: 10.1524/zpch.2012.0287
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Order and Dynamics of Tris(2-ethylhexyl)phosphate Confined in Uni-Directional Nanopores

Abstract: Infrared Transition Moment Orientational Analysis (IR–TMOA) and Broadband Dielectric Spectroscopy (BDS) are combined to study molecular order and dynamics of the glass-forming liquid Tris(2-ethylhexy)phosphate (TEHP) confined in uni-directional nanopores with diameters of 4, 8, and 10.4 nm. The former method enables one to determine the molecular order parameter of specific IR transition moments. It is observed that the central P=O moiety of TEHP has a weak orientational effect (molecular order parameter S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(66 citation statements)
references
References 19 publications
2
63
1
Order By: Relevance
“…To obtain the effective dielectric strength for confined molecules, a model of two impedances in parallel was employed as described in detail elsewhere. 31 Fourier transform infrared (FTIR) absorption measurements were carried out using a Bio-Rad FTS 6000 spectrometer from 700 cm −1 to 5000 cm −1 with a resolution of 2 cm −1 . The temperature was controlled with an uncertainty of less than 0.5 K by means of a Linkam THMS 600 cell equipped with ZnSe windows.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain the effective dielectric strength for confined molecules, a model of two impedances in parallel was employed as described in detail elsewhere. 31 Fourier transform infrared (FTIR) absorption measurements were carried out using a Bio-Rad FTS 6000 spectrometer from 700 cm −1 to 5000 cm −1 with a resolution of 2 cm −1 . The temperature was controlled with an uncertainty of less than 0.5 K by means of a Linkam THMS 600 cell equipped with ZnSe windows.…”
Section: Methodsmentioning
confidence: 99%
“…The significance of the contribution of intramolecular interaction to dynamic glass transition has been recently proven by a combination of Broadband Dielectric Spectroscopy (BDS) and Fourier-Transform Infrared (FTIR) spectroscopy. [29][30][31] This approach has been employed to study liquid crystals under confinement, 32 glass transition of low molecular weight, 29,30,33 and polymeric systems 30,34 in bulk. It has been reported that various 0021-9606/2018/149(6)/064501/9/$30.00…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports by the group of Kremer 16 18 also demonstrated that the splitting of the structural and secondary relaxation processes at T c is very often accompanied by the change in intramolecular dynamics. Therefore, to address this issue additional temperature-dependent FTIR measurements above and below T c were carried out to follow intramolecular dynamics in L-sorbose.…”
Section: Resultsmentioning
confidence: 96%
“…Similar observations, but without special explanation, have been also reported by Kaminski et al . 35 and the group of Kremer 17 , 18 . Such correspondence between intra- and intermolecular dynamics was found much above the glass transition temperature ( T ≈ 1.2 T g ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation